Analyzing the persistent nature of quality issues in low-cost housing projects - Sibiya, Zandile Agnes (My University, 2018)
The primary objective of this research was to investigate the progressiveness of housing policies and strategies in addressing persistent quality defect challenges experienced in low cost housing projects delivered by the Department of Human Settlements (DHS). As low cost housing projects continue to dominate the South African housing market for low to middle income households and millions spent on rectifications, it was imperative to question why achieving defect-free housing project is such a challenge. Through employing mixed research methods, the researcher found that there has been a noticeable decrease in the frequency of defects due to the introduction of the NHBRC (project and home enrolment) process and the warranty scheme. However, common cases of non-enrolment and late enrolments of housing projects results in non-compliant houses and reinforce the persistence of the defective stock. Furthermore, it was found through the research that a large historical defective stock also remains, which forms the bulk of the defective stock that was accumulated prior to the introduction of the NHBRC warranty scheme and has proved difficult to eradicate due to budgetary constraints. In conclusion, the researcher argues that the delayed rectification of the defective stock and the persistence of quality management challenges continues to threaten the sustainability and viability of the entire Human Settlements programme. It is also clear that the regulatory role of the NHBRC in ensuring and enforcing quality compliance is being hampered by inefficient quality management processes caused by organizational and project management challenges of the DHS, which can be addressed by employing wholesome quality management systems such as TQM.
A Research Report submitted to the Faculty of Engineering and Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science (Building),2018